Echoes of Loss: Examining Gendered Violence and Legacy in the Armenian Genocide - Ozlem Karakus (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
This article explores the intergenerational transmission of memories among descendants of Armenian Genocide survivors, focusing on perspectives from both males and females. Using an oral history methodology in three provinces– Erznka (modern-day Erzincan), Malatya, and Dersim – the study investigates how narratives of the genocide have been passed down and changed within families. The research emphasizes the gender-specific tactics of the genocide, where Armenian men were often targeted for extermination, while women and children endured forced marches, sexual violence, abductions and forced marriages. By connecting with descendants who carry the post-memory of these events, the study reveals the deep and lasting impact of these atrocities on the Armenian community. Their stories unveil the intricate layers of trauma and resilience that define the Armenian experience and contribute to a broader understanding of genocide and its enduring effects on future generations.
Keywords: Armenian Genocide